Josua und Salomo : eine Studie zu Autorität und Legitimität des Nachfolgers im Alten Testament - Schafer-Lichtenberger, Christa. (Vetus Testamentum, Supplements, 1995)
Josua und Salomo puts forward the thesis that the literary figure of the successor was created by circles who strongly relied on the book of Deuteronomy. In order to construct the ideal of a successor they used the characters of Joshua and Solomon and implemented the results of their theological reflection which were unleashed by the complete destruction of the pre-exilic political, social and religious organization of the nation. The figure of Joshua combines all the treats of their theological conception of an ideal political leader, whereas the figure of Solomon demonstrates the dangers which are implied in monarchical succession. From the theological perspective of deuteronomism "Solomon" and "Joshua" are opposite characters. The deuteronomic concepts of God and authority play a central role for the reflection on both characters.